2020
DOI: 10.3390/jcm9082361
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Functions During Extracorporeal Membrane Oxygenation. Platelet–Leukocyte Aggregates Analyzed by Flow Cytometry as a Promising Tool to Monitor Platelet Activation

Abstract: Extracorporeal membrane oxygenation (ECMO) is an extracorporeal circulation used to manage patients with severe circulatory or respiratory failure. It is associated with both high bleeding and thrombosis risks, mainly as a result of biomaterial/blood interface phenomena, high shear stress, and complex inflammatory response involving the activation of coagulation and complement systems, endothelial cells, leukocytes, and platelets. Besides their critical role in hemostasis, platelets are important players in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…However, thrombocytes have been reported to also liberate IL1β upon stimulation [35]. There is a strong mutual interaction and activation between platelets and leukocytes (especially neutrophils and macrophages) [36]. Therefore, the increase in leukocyte numbers only in the cotton group during HLM is likely related to the stimulation of proliferation and differentiation of neutrophil precursors by IL1β [30], which is released by either monocytes or platelets and can induce the mobilization of granulocyte progenitor cells and maturation of neutrophils in the bone marrow [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thrombocytes have been reported to also liberate IL1β upon stimulation [35]. There is a strong mutual interaction and activation between platelets and leukocytes (especially neutrophils and macrophages) [36]. Therefore, the increase in leukocyte numbers only in the cotton group during HLM is likely related to the stimulation of proliferation and differentiation of neutrophil precursors by IL1β [30], which is released by either monocytes or platelets and can induce the mobilization of granulocyte progenitor cells and maturation of neutrophils in the bone marrow [37].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is produced by activated monocytes [41]. Activated platelets secrete thrombocyte activating (e.g., platelet-activating factor, ADP, von Willebrand Factor, [42]) but also neutrophil-activating (neutrophil-activating peptide 2) and other inflammation-triggering mediators such as reactive oxygen species [36]. Therefore, the significantly higher activation of platelets, measured by β-TG release, in blood wrung from cotton could be responsible for the increased neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a study documented that the inhibition of integrin aIIbb3 by tirofiban could significantly reduce the platelet-eosinophil aggregates and pulmonary eosinophil infiltration in allergic airways and reduce airway hyperresponsiveness and inflammation (72). Mechanistic studies further indicated that Mac-1 on eosinophils could interact with integrin aIIbb3 through a bridge molecule such as fibrinogen and sCD40L (73,74).…”
Section: Roles Of Platelet-eosinophil Interactions In Allergic Asthmamentioning
confidence: 99%
“…Balle et al demonstrated that patients with extracorporeal procedures have a reduced platelet adhesion, activation, and platelet aggregation during the ongoing procedure. 15,16 However, only limited data of published studies exist on this topic. So, we would like to introduce a sensitive and easy-to-use method to determine platelet activation status in whole blood (WB) after shear stress simulation, as by ECC, which may be helpful to assess the risk of both bleeding and thrombosis.…”
Section: Introductionmentioning
confidence: 99%